Pengaruh profitabilitas, leverage, ukuran perusahaan dan sales growth terhadap tax avoidance - Faradilla, Ivory Candra; Bhilawa, Loggar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The goal of this essay is to find how tax evasion is affected by profitability, leverage, firm size, and sales growth. The population used in this form of quantitative study is the LQ45 corporation for the 2015-2021 timeframe. The study approach employs a purposive sampling technique, with a sample size of 80 data points from 22 organizations. For linear regression data analysis, SPSS 23 software is used. The f test was used in this study, yielding a result of < 0,05, indicating that the significant value of the variables of profitability, leverage, business size, and sales growth had an effect on tax evasion. Based on partial testing of profitability, leverage, and company size variables with a significance value of <0.05, it is possible to infer that these factors have an influence. While the sales growth variable has a significance value greater than 0,05, it may be assumed that it has no influence.